A kind of recycled aggregate negative carbon permeable concrete and preparation method thereof

By using special gels and Bacillus colloidal powder in regenerated aggregate permeable concrete, the problem of regenerated aggregate permeable concrete being affected during cement hydration and weakening of ITZ adhesion, the effect of improving the carbonization strength and carbon absorption and carbon sequestration ability of concrete is achieved.

CN119349965BActive Publication Date: 2025-03-11CHINA CONSTR WESTERN CONSTR (GUANGDONG) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411931561.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Recycled aggregate permeable concrete is affected in the cement hydration process, and its ITZ weakens its bonding force, resulting in low strength, making it difficult to widely develop and utilize.

Method used

The special gel was prepared from composite C2S with slag and polyoxyethylene (5) nonylphenyl ether, and the gel was cured by high-pressure spraying and low-frequency microwave drying, and the aggregate was modified and regenerated to improve hardness and fill microcracks, while Bacillus colloidal powder was introduced to accelerate the CO2 hydration reaction.

Benefits of technology

The carbonization strength and carbon absorption and carbon sequestration ability of concrete are improved, the hardness of regenerated aggregates is enhanced, and microcracks are filled, improving the mechanical properties and water permeability of concrete.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a recycled aggregate negative carbon permeable concrete and a preparation method thereof, and relates to the field of permeable concrete. The recycled aggregate negative carbon permeable concrete includes the following components by mass: 1186-1423 parts of recycled coarse aggregate, 54-68 parts of fine aggregate, 221-263 parts of cement, 147-175 parts of fly ash, 111-132 parts of water, 3.37-4.01 parts of water reducer, 263-285 parts of special gel, and 3.68-4.38 parts of bacterial powder. The recycled aggregate negative carbon permeable concrete, by wrapping the special gel on the surface of the recycled aggregate and introducing bacterial powder with biological enzyme catalysis, improves the hardness of the recycled aggregate and closes microcracks and pores, not only effectively improves the mechanical properties of the permeable concrete, but also gives the permeable concrete carbon absorption and carbon fixation performance, realizes low-carbon and environmentally friendly production, and conforms to the current environmental protection and dual-carbon concepts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of permeable concrete, and in particular to a recycled aggregate negative carbon permeable concrete and a preparation method thereof. Background Art

[0002] Permeable concrete is an important green raw material for building sponge cities. It can not only timely infiltrate road surface water to the underground or water storage device through its unique porous structure, but also has the functions of sound absorption and noise reduction, anti-glare, and reducing urban heat island effect. Secondly, the porous structure of permeable concrete also determines that its cement consumption per cubic meter is less than that of ordinary concrete. Therefore, using recycled permeable pavement instead of ordinary concrete on non-heavy roads can not only effectively solve the problem of urban waterlogging, but also greatly help reduce carbon emissions.

[0003] The reason why recycled aggregate pervious concrete has not been widely developed and utilized is that, firstly, there are many micro cracks inside the recycled aggregate, the porosity is high, and the water absorption itself is strong, which affects the cement hydration process of pervious concrete. Secondly, the strength of pervious concrete itself is low, and it mostly depends on the strength of the transition zone between cement paste and aggregate interface (ITZ). The ITZ of recycled aggregate pervious concrete has a transition zone between new and old cement pastes, and the bonding force is greatly weakened, resulting in lower strength. Summary of the invention

[0004] The purpose of the present invention is to provide a recycled aggregate negative carbon permeable concrete to solve the problems raised in the above background technology.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a recycled aggregate negative carbon permeable concrete, comprising the following components by mass: 1186-1423 parts of recycled coarse aggregate, 54-68 parts of fine aggregate, 221-263 parts of cement, 147-175 parts of fly ash, 111-132 parts of water, 3.37-4.01 parts of water reducer, 263-285 parts of special gel, and 3.68-4.38 parts of bacterial powder.

[0006] Preferably, the particle size of the recycled coarse aggregate is 5-10 mm, with single particle grading.

[0007] Preferably, the fly ash is Grade I fly ash, and the bacterial powder is Bacillus subtilis powder with an activity of 4.5×10 9 cell / g-6.0×10 9 cell / g.

[0008] Preferably, the special gel is a composite C2S gel.

[0009] Preferably, the special gel comprises the following components by mass: 30-60 parts of slag, 30-45 parts of polyoxyethylene (5) nonylphenyl ether, 3-6 parts of hydroxypropyl methylcellulose, and 85-105 parts of composite C2S mineral powder.

[0010] Preferably, the composite C2S ore powder is obtained by compounding pure γ-C2S ore powder and pure β-C2S ore powder, and the compounding weight ratio is γ-C2S:β-C2S=3-4:7-6.

[0011] Preferably, the Bacillus subtilis powder is obtained by atomizing the original bacterial liquid using calcium carbonate as a carrier and sodium sulfate as a nutrient.

[0012] Preferably, the bacterial concentration of the bacterial solution is 1.5×10 7 ~10 8 cells / mL.

[0013] Preferably, the method for preparing the special gel comprises the following steps:

[0014] S1. The slag and the composite C2S ore powder are dried to a constant weight and then mixed and ground to obtain a mixed material;

[0015] S2. The mixed material is added with polyoxyethylene (5) nonylphenyl ether and stirred until the powder is completely dissolved, and then water is added to dissolve and stirred to obtain a mixture;

[0016] S3. Add hydroxypropyl methylcellulose to the mixture and continue stirring to obtain a special gel.

[0017] Preferably, a method for preparing recycled aggregate negative carbon permeable concrete comprises the following steps:

[0018] SS1. Pre-treat the recycled coarse aggregate: use high-pressure spraying to coat the surface of the recycled coarse aggregate with a layer of special gel, and then use low-frequency microwave drying to solidify the gel to obtain modified recycled coarse aggregate;

[0019] SS2. First, mix the modified recycled coarse aggregate, fine aggregate and 10% water in a mixer for 30 seconds to fully pre-wet the aggregate, then add cement, fly ash and bacterial powder and mix for 60 seconds to mix the aggregate and powder evenly;

[0020] SS3. Add the remaining 90% water and water reducing agent and stir. After stirring, observe the mixing condition to obtain recycled aggregate negative carbon permeable concrete.

[0021] Technical effects and advantages of the present invention:

[0022] 1. The present application uses a special gel prepared from composite C2S, slag and polyoxyethylene (5) nonylphenyl ether with strong affinity for carbon dioxide; on the one hand, the composite C2S group is optimized by compounding pure γ-C2S ore powder and pure β-C2S ore powder, and the characteristic of γ-C2S that it will not undergo hydration reaction but will undergo carbonation reaction with CO2 before β-C2S is utilized, and the heat released by the carbonation reaction of γ-C2S is used to accelerate the Ca2+ conversion of β-C2S in the composite C2S group. 2+ The dissolution rate of γ-C2S is increased, and the carbonation reaction and hydration process of β-C2S are accelerated and enhanced. The carbonation strength and degree of concrete are improved through the synergistic effect of γ-C2S and β-C2S. At the same time, the activity of slag can be further stimulated during the carbonation process of gel absorbing CO2, and the mechanical properties of concrete will be further improved after the gel containing slag solidifies. On the other hand, by high-pressure spraying, the gel is evenly wrapped on the recycled aggregate, and the gel is solidified by low-frequency microwave drying. While improving the hardness of the recycled aggregate, it can also fill and seal the micro cracks or pores on the recycled aggregate, reducing the impact of the high water absorption of the recycled aggregate on the concrete mix design, mixing and later performance. By utilizing the porous structure of the recycled aggregate itself and the carbon dioxide affinity of polyoxyethylene (5) nonylphenyl ether, the adsorption capacity of carbon dioxide can be further improved in the structure.

[0023] 2. The present application uses a bacterial powder made of Bacillus colloids wrapped in an inorganic carrier. Bacillus colloids can secrete carbonic anhydrase (CA), which is a Zn-containing metal enzyme that accelerates the hydration of CO2 to generate HCO3. - Theoretically, it can accelerate the CO2 hydration reaction rate by about 0.77×10 7 times, which can significantly improve CO2 adsorption and fixation.

[0024] H2O+CO2⇌HCO3 - +H +

[0025] Under the enzyme catalysis of Bacillus subtilis, the slag in the gel can fix CO2 in mineral form, further improving the carbon fixation efficiency and rate of the slag. At the same time, the introduction of Bacillus subtilis powder into recycled aggregate permeable concrete, using the porous characteristics of recycled aggregate permeable concrete at both macro and micro levels, provides Bacillus subtilis with a larger contact surface with CO2 in the environment, further improving the absorption rate and efficiency of CO2. DETAILED DESCRIPTION

[0026] In order to explain the technical solution of the present invention in detail, the technical solution of the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The recycled aggregate negative carbon permeable concrete provided in the following embodiments and comparative examples, the selected cement is ordinary Portland cement with a P·O42.5; the selected recycled coarse aggregate has a particle size of 5-10 mm single particle grading; the selected recycled fine aggregate is machine-made sand with a fineness modulus of 2.5; the selected fly ash is Class I fly ash; the selected water reducer is SPC-100 polycarboxylic acid high-performance water reducer; the selected polyoxyethylene (5) nonylphenyl ether has a purity of Igepal CO-520%.

[0028] The preparation method of the recycled aggregate negative carbon permeable concrete selected in the following examples and comparative examples is:

[0029] SS1. Pre-treat the recycled coarse aggregate: Use high-pressure spraying to coat the surface of the recycled coarse aggregate with a layer of special gel, and then use low-frequency microwave drying to solidify the gel to obtain modified recycled coarse aggregate.

[0030] SS2. First, mix the modified recycled coarse aggregate, fine aggregate and 10% water in a mixer for 30 seconds to fully pre-wet the aggregate, then add cement, fly ash and bacterial powder and mix for 60 seconds to mix the aggregate and powder evenly.

[0031] SS3. Add the remaining 90% water and water reducing agent and stir. After stirring, observe the mixing condition to obtain recycled aggregate negative carbon permeable concrete.

[0032] Example 1

[0033] The present embodiment provides a recycled aggregate negative carbon permeable concrete, whose raw materials include: 1186 parts of recycled coarse aggregate, 60 parts of fine aggregate, 221 parts of cement, 158 parts of fly ash, 111 parts of water, 3.54 parts of water reducer, 263 parts of special gel, and 3.92 parts of bacterial powder.

[0034] The preparation method of the special gel is:

[0035] S1. 30 parts of slag and 90 parts of composite C2S ore powder with a ratio of γ-C2S:β-C2S=4:6 are dried to constant weight and then mixed and ground to obtain a mixed material.

[0036] S2. Add 30 parts of polyoxyethylene (5) nonylphenyl ether to the mixed material and continue stirring until the powder is completely dissolved, then add 130 parts of water to dissolve and continue stirring to obtain a mixture.

[0037] S3. Add 3 parts of hydroxypropyl methylcellulose to the mixture and continue stirring to obtain a special gel.

[0038] The activity of the bacterial powder is 5.0×10 9 cell / g.

[0039] Example 2

[0040] The present embodiment provides a recycled aggregate negative carbon permeable concrete, whose raw materials include: 1328 parts of recycled coarse aggregate, 68 parts of fine aggregate, 242 parts of cement, 175 parts of fly ash, 124 parts of water, 4.01 parts of water reducer, 274 parts of special gel, and 4.38 parts of bacterial powder.

[0041] The preparation method of the special gel is:

[0042] S1. 45 parts of slag and 105 parts of composite C2S ore powder with a ratio of γ-C2S:β-C2S=3:7 are dried to constant weight and then mixed and ground to obtain a mixed material.

[0043] S2. Add 40 parts of polyoxyethylene (5) nonylphenyl ether to the mixed material and continue stirring until the powder is completely dissolved, then add 150 parts of water to dissolve and continue stirring to obtain a mixture.

[0044] S3. Add 5 parts of hydroxypropyl methylcellulose to the mixture and continue stirring to obtain a special gel.

[0045] The activity of the bacterial powder is 6.0×10 9 cell / g.

[0046] Example 3

[0047] The present embodiment provides a recycled aggregate negative carbon permeable concrete, whose raw materials include: 1423 parts of recycled coarse aggregate, 54 parts of fine aggregate, 263 parts of cement, 147 parts of fly ash, 132 parts of water, 3.37 parts of water reducer, 285 parts of special gel, and 3.68 parts of bacterial powder.

[0048] The preparation method of the special gel is:

[0049] S1. 60 parts of slag and 85 parts of composite C2S ore powder prepared in a ratio of γ-C2S:β-C2S=4:6 are dried to constant weight and then mixed and ground to obtain a mixed material.

[0050] S2. Add 45 parts of polyoxyethylene (5) nonylphenyl ether to the mixed material and continue stirring until the powder is completely dissolved, then add 110 parts of water to dissolve and continue stirring to obtain a mixture.

[0051] S3. Add 6 parts of hydroxypropyl methylcellulose to the mixture and continue stirring to obtain a special gel.

[0052] The activity of the bacterial powder is 4.5×10 9 cell / g.

[0053] Example 4

[0054] The present embodiment provides a recycled aggregate negative carbon permeable concrete, whose raw materials include: 1186 parts of recycled coarse aggregate, 68 parts of fine aggregate, 221 parts of cement, 175 parts of fly ash, 111 parts of water, 4.01 parts of water reducer, 263 parts of special gel, and 4.38 parts of bacterial powder.

[0055] The preparation method of the special gel is:

[0056] S1. 30 parts of slag and 105 parts of composite C2S ore powder with a ratio of γ-C2S:β-C2S=3:7 are dried to constant weight and then mixed and ground to obtain a mixed material.

[0057] S2. Add 30 parts of polyoxyethylene (5) nonylphenyl ether to the mixed material and continue stirring until the powder is completely dissolved, then add 150 parts of water to dissolve and continue stirring to obtain a mixture.

[0058] S3. Add 3 parts of hydroxypropyl methylcellulose to the mixture and continue stirring to obtain a special gel.

[0059] The activity of the bacterial powder is 6.0×10 9 cell / g.

[0060] Example 5

[0061] The present embodiment provides a recycled aggregate negative carbon permeable concrete, whose raw materials include: 1342 parts of recycled coarse aggregate, 61 parts of fine aggregate, 245 parts of cement, 163 parts of fly ash, 126 parts of water, 3.64 parts of water reducer, 273 parts of special gel, and 3.97 parts of bacterial powder.

[0062] The preparation method of the special gel is:

[0063] S1. 41 parts of slag and 96 parts of composite C2S ore powder prepared in a ratio of γ-C2S:β-C2S=4:6 are dried to constant weight and then mixed and ground to obtain a mixed material.

[0064] S2. Add 48 parts of polyoxyethylene (5) nonylphenyl ether to the mixed material and continue stirring until the powder is completely dissolved, then add 128 parts of water to dissolve and continue stirring to obtain a mixture.

[0065] S3. Add 5 parts of hydroxypropyl methylcellulose to the mixture and continue stirring to obtain a special gel.

[0066] The activity of the bacterial powder is 5.0×10 9 cell / g.

[0067] Example 6

[0068] The difference from Example 3 is that the weight ratio of the composite mineral powder is γ-C2S:β-C2S=3:7.

[0069] Example 7

[0070] The difference from Example 3 is that the polyoxyethylene (5) nonylphenyl ether in the gel preparation raw material is replaced by lauryl alcohol polyoxyethylene ether.

[0071] Example 8

[0072] The difference from Example 3 is that no surfactant such as polyoxyethylene (5) nonylphenyl ether or lauryl alcohol polyoxyethylene ether is added to the raw materials for preparing the gel.

[0073] Example 9

[0074] The difference from Example 3 is that the activity of the bacterial powder is 5.0×10 9 cell / g.

[0075] Example 10

[0076] The difference from Example 3 is that the activity of the bacterial powder is 4.0×10 9 cell / g.

[0077] Comparative Example 1

[0078] The difference from Example 3 is that no slag is added to the special gel of Comparative Example 1.

[0079] Comparative Example 2

[0080] The difference from Example 3 is that the ratio of the composite C2S mineral powder in the special gel is γ-C2S:β-C2S=1:9

[0081] Comparative Example 3

[0082] The difference from Example 3 is that the composite C2S mineral powder in the special gel is completely replaced by pure γ-C2S mineral powder.

[0083] Comparative Example 4

[0084] The difference from Example 3 is that the composite C2S mineral powder in the special gel is completely replaced by pure β-C2S mineral powder.

[0085] Comparative Example 5

[0086] The difference from Example 3 is that no special gel is added to the raw materials.

[0087] Comparative Example 6

[0088] The difference from Example 3 is that no bacterial powder is added to the raw materials.

[0089] Performance testing

[0090] 1. Concrete mechanical properties test: Test the 28d cube compressive strength and splitting tensile strength of concrete according to the mechanical properties test method in GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete".

[0091] 2. Concrete permeability test: Determine the 28d permeability coefficient of concrete according to the permeability coefficient determination method in CJJ / T135-2009 "Technical Code for Permeable Cement Concrete Pavement".

[0092] 3. Concrete carbon absorption and carbon fixation ability test: The recycled aggregate permeable concrete mixed in each embodiment and the comparative example is made into a cube of 150mm×150mm×150mm, and the mass of the test block at 28d is recorded as the original mass, and the mass at 90d under normal temperature and pressure is the mass after carbonization, and the mass loss rate (%) is calculated. After the concrete absorbs carbon dioxide, calcium carbonate will be generated in the matrix, resulting in an increase in the mass of the concrete. The carbon absorption and carbon fixation ability of the concrete is evaluated by the mass loss rate. When the mass loss rate is less than 5%, it is determined that the concrete has the performance of carbon absorption and carbon fixation. When the mass loss rate is a negative number, it means that the mass has increased and the carbon absorption and carbon fixation ability is stronger.

[0093] 4. Test of carbon dioxide release during curing: The concrete mixed in each embodiment and comparative example was made into a cubic test block of 150 mm × 150 mm × 150 mm, and cured for 28 days after demolding. During the curing process, a portable infrared carbon dioxide monitor was used to monitor the carbon dioxide concentration in the curing room. The initial carbon dioxide concentration in the curing room was 585 ppm. The carbon dioxide concentrations in the curing room were recorded when the test blocks were cured for 3 days, 14 days, and 28 days. When the carbon dioxide concentration was less than 725 ppm, it indicated that the concrete had carbon absorption capacity, and when it was greater than 950 ppm, it indicated that the concrete released more carbon dioxide.

[0094] Table 1

[0095] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 28d compressive strength / MPa 31.3 31.9 33.9 31.2 32.8 33.4 32.3 30.9 31.6 28d splitting tensile strength / MPa 4.27 4.36 4.67 4.30 4.55 4.51 4.38 4.25 4.31 <![CDATA[28d permeability coefficient / mm·s -1 > 2.69 2.86 2.54 2.67 2.29 2.51 2.70 2.53 2.72 Test items Example 10 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 28d compressive strength / MPa 32.6 21.9 28.9 30.1 26.3 19.7 29.8 28d splitting tensile strength / MPa 4.43 2.89 3.86 4.11 3.43 2.67 3.97 <![CDATA[28d permeability coefficient / mm·s -1 > 2.32 3.78 2.69 2.79 2.84 4.26 3.01

[0096] Table 2

[0097] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Quality loss rate / % -0.168 -0.191 -0.246 -0.174 -0.216 -0.241 -0.208 -0.157 -0.169 <![CDATA[3d CO2 concentration]]> 663PPM 648PPM 609PPM 657PPM 627PPM 614PPM 637PPM 674PPM 632PPM <![CDATA[14d CO2 concentration]]> 629PPM 617PPM 584PPM 624PPM 601PPM 591PPM 608PPM 641PPM 617PPM <![CDATA[28d CO2 concentration]]> 601PPM 583PPM 554PPM 598PPM 574PPM 567PPM 576PPM 607PPM 609PPM Test items Example 10 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Quality loss rate / % -0.209 -0.196 -0.094 -0.164 -0.064 0.68 -0.141 <![CDATA[3d CO2 concentration]]> 634PPM 642PPM 734PPM 666PPM 760PPM 762PPM 681PPM <![CDATA[14d CO2 concentration]]> 604PPM 613PPM 716PPM 618PPM 748PPM 898PPM 652PPM <![CDATA[28d CO2 concentration]]> 580PPM 585PPM 701PPM 614PPM 741PPM 1034PPM 621PPM

[0098] By comparing the performance indicators of Example 3 and Example 6, the following conclusions can be drawn: when the composite mineral powder has a weight ratio of γ-C2S: β-C2S = 3:7 or 4:6, the mechanical properties and carbon absorption and carbon fixation properties of the recycled aggregate negative carbon permeable concrete can be well taken into account, and when the weight ratio of the composite mineral powder is γ-C2S: β-C2S = 4:6, the performance is even better, indicating that the synergistic effect of γ-C2S and β-C2S is stronger at this composite ratio, and the heat released by the carbonation reaction of γ-C2S accelerates the Ca2+ conversion of β-C2S in the composite C2S group. 2+ The dissolution rate of β-C2S is accelerated and enhanced, and the carbonation reaction and hydration process of β-C2S are accelerated and enhanced.

[0099] The following conclusions can be drawn from the various performance indicators of Example 3 and Example 7, Example 3 and Example 8: ① When the surfactant polyoxyethylene (5) nonylphenyl ether with strong carbon dioxide affinity in the gel preparation raw material described in Example 3 is replaced with lauryl alcohol polyoxyethylene ether, the carbon capture capacity is reduced, and the rate and total amount of matrix absorption of CO2 are reduced, resulting in the mechanical properties and carbon absorption and carbon fixation performance of the recycled aggregate negative carbon permeable concrete being reduced to varying degrees; ② When the surfactant component in the gel preparation raw material described in Example 3 is removed, the mechanical properties and carbon absorption and carbon fixation performance of the recycled aggregate negative carbon permeable concrete are significantly reduced, because there is a lack of surface active components, and the slag is unevenly dispersed in the gel and agglomerates, resulting in weak parts of the gel after coagulation and solidification, and it is not good to provide strength supplement for the recycled aggregate and concrete matrix. At the same time, the agglomeration of the slag also reduces the effect of accelerating carbonization by the catalytic action of the Bacillus colloidus enzyme.

[0100] Comparing the performance indicators of Example 3 and Example 9, and Example 3 and Example 10, the following conclusions can be drawn: The enzyme catalysis of Bacillus colloids can accelerate the hydration of CO2 to generate HCO3 -, promoting the CO2 hydration reaction rate, significantly improving CO2 adsorption and fixation. However, this effect is not directly positively correlated with the activity of the bacterial powder. It can be seen from the performance test results of Examples 3, 9, and 10 that the mechanical properties and carbon absorption and fixation properties of the recycled aggregate negative carbon permeable concrete first increase and then decrease with the increase of bacterial powder activity. This is mainly because the bacterial powder contains more sodium sulfate, and the slag contains part of sulfoaluminate. When the bacterial powder is added in excess, a large amount of sodium sulfate will react with sulfoaluminate to form hydrated calcium sulfoaluminate (AFm), which will further fill the micropores inside the matrix and improve the internal density, so that the matrix obtains a higher early strength. However, at the same time, since the internal pores are filled, the channel for CO2 transmission will inevitably be blocked, hindering the absorption of CO2. The composite mineral powder and slag in the gel have a low degree of carbonization, which is a weak reinforcement ability for the later strength of the concrete.

[0101] Combining the various performance indicators of Example 3 and Comparative Example 1, the following conclusions can be drawn: without adding slag to the components of the special gel, the mechanical properties are greatly reduced, and the amount of adsorbed and fixed carbon dioxide is slightly reduced.

[0102] Combining the various performance indicators of Example 3 and Comparative Example 2, the following conclusions can be drawn: when the ratio of composite C2S mineral powder in the special gel is γ-C2S:β-C2S=1:9, the mechanical properties of the concrete prepared are slightly reduced, the amount of adsorbed and fixed carbon dioxide is greatly reduced, and the carbon absorption and carbon fixation capacity of the concrete is low.

[0103] Combining the various performance indicators of Example 3 and Comparative Example 3, the following conclusions can be drawn: when the composite C2S mineral powder in the special gel is completely replaced by pure γ-C2S mineral powder, the mechanical properties and the amount of adsorbed and fixed carbon dioxide of the concrete prepared are reduced to a certain extent. Lacking the synergistic effect of γ-C2S and β-C2S, the carbonization strength and degree of carbonization of the concrete cannot be further supplemented.

[0104] Combining the various performance indicators of Example 3 and Comparative Example 4, the following conclusions can be drawn: when the composite C2S mineral powder in the special gel is completely replaced by pure β-C2S mineral powder, the mechanical properties of the prepared concrete are greatly reduced, and the amount of adsorbed and fixed carbon dioxide is greatly reduced. When there is only β-C2S, there is a lack of thermal excitation in the carbonation process of γ-C2S, and the carbonation and hydration rates of β-C2S are slow, and the carbonation strength and degree of carbonization of the concrete cannot be further supplemented.

[0105] Combining the various performance indicators of Example 3 and Comparative Example 5, the following conclusion can be drawn: the concrete prepared without adding the special gel cannot achieve the effect of carbon absorption and carbon fixation, aggravating the carbon dioxide emission in the urban environment, and therefore does not have the performance that carbon absorption and carbon fixation concrete should have.

[0106] Combining the performance indicators of Example 3 and Comparative Example 6, the following conclusions can be drawn: the mechanical properties and adsorption and fixation of carbon dioxide in the concrete prepared without the addition of bacterial powder are greatly reduced. The above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. Any modification or equivalent replacement made within the spirit and principles of the present invention.

Claims

1. A recycled aggregate negative carbon permeable concrete, characterized in that: The components include the following by mass: 1186-1423 parts of recycled coarse aggregate, 54-68 parts of fine aggregate, 221-263 parts of cement, 147-175 parts of fly ash, 111-132 parts of water, 3.37-4.01 parts of water reducer, 263-285 parts of special gel, 3.68-4.38 parts of bacterial powder, wherein the special gel is a composite C2S gel, and the bacterial powder is a colloid Bacillus powder; The special gel comprises the following components by mass: 30-60 parts of slag, 30-45 parts of polyoxyethylene (5) nonylphenyl ether, 3-6 parts of hydroxypropyl methylcellulose, and 85-105 parts of composite C2S mineral powder; The composite C2S ore powder is obtained by compounding pure γ-C2S ore powder and pure β-C2S ore powder, and the compounding weight ratio is γ-C2S:β-C2S=3-4:7-6; The preparation method of the special gel comprises the following steps: S1. The slag and the composite C2S ore powder are dried to constant weight and then mixed and ground to obtain a mixed material; S2. The mixed material is added with polyoxyethylene (5) nonylphenyl ether and stirred until the powder is completely dissolved, and then water is added to dissolve and stirred to obtain a mixture; S3. Hydroxypropyl methylcellulose was added to the mixture and stirring was continued to obtain a special gel; The preparation method of recycled aggregate negative carbon permeable concrete comprises the following steps: SS1. Pre-treat the recycled coarse aggregate: use high-pressure spraying to coat the surface of the recycled coarse aggregate with a layer of special gel, and then use low-frequency microwave drying to solidify the gel to obtain modified recycled coarse aggregate; SS2. First, mix the modified recycled coarse aggregate, fine aggregate and 10% water in a mixer for 30 seconds to fully pre-wet the aggregate, then add cement, fly ash and bacterial powder and mix for 60 seconds to mix the aggregate and powder evenly; SS3. Add the remaining 90% water and water reducing agent and stir. After stirring, observe the mixing condition to obtain recycled aggregate negative carbon permeable concrete.

2. The recycled aggregate negative carbon permeable concrete according to claim 1, characterized in that: The particle size of the recycled coarse aggregate is 5-10 mm, with single particle grading.

3. The recycled aggregate negative carbon permeable concrete according to claim 1, characterized in that: The fly ash is Grade I fly ash, and the activity of the bacterial powder is 4.5×10 9 cell / g-6.0×10 9 cell / g.

4. The recycled aggregate negative carbon permeable concrete according to claim 3, characterized in that: The gelatinous bacillus powder is obtained by atomizing the original bacterial liquid with calcium carbonate as a carrier and sodium sulfate as a nutrient.

5. The recycled aggregate negative carbon permeable concrete according to claim 4, characterized in that: The bacterial concentration of the bacterial solution was 1.5×10 7 ~10 8 cells / mL.

Citation Information

Patent Citations

  • Renewable environment-friendly pervious concrete and preparation method thereof

    CN111908862A

  • Asphalt waste powder-based low-carbon water permeable brick and preparation method thereof

    CN116177952A